KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCACATAN SIPIL KOTA DENPASAR DI TENGAH SITUASI PANDEMI COVID-19 - Ni Nyoman Ariani; Anak Agung Putu Sugiantiningsih; Moch. Noor; I Gde Oka Saputra (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2021)
Many people have adapted to the situation of covid-19 outbreak including public service providers. Government policies to prevent the spread of COVID-19 have an impact on public service standards implemented by the service providers. Regarding this matter, this study was conducted to analyze the quality of the service provided by Civil Registry Office of Denpasar during covid-19 pandemic. Interviews and direct observations were carried out to collect data. In this data collection process, five questions were given to six informants at this Office. The results of this study show that any declines in terms of the quality of the public services provided by this Office are not identified.